Recent advances in the therapeutic perspectives of Nutlin-3. - Secchiero, Paola; Bosco, Raffaella; Celeghini, Claudio; Zauli, Giorgio (Curr Pharm Des, 2011)
Nutlin-3 is a small molecule inhibitor of the MDM2/p53 interaction, which leads to the non-genotoxic p53 stabilization, activation of cell cycle arrest and apoptosis pathways. A series of recent studies have strengthened the concept that selective, non-genotoxic p53 activation by Nutlin-3 might represent an alternative to the current cytotoxic chemotherapy, in particular for pediatric tumors and for hematological malignancies, which retain a high percentage of p53(wild-type) status at diagnosis. Like most other drugs employed in cancer therapy, it will be unlikely that Nutlin-3 will be used as a monotherapy. In this respect, Nutlin-3 shows a synergistic cytotoxic effect when used in combination with innovative drugs, such as TRAIL or bortozemib. Although Nutlin-3 is currently in phase I clinical trial for the treatment of retinoblastoma, its effects on normal tissues and cell types remain largely to be determined and will require further investigation in the future years.
Keywords: Antineoplastic Agents; Antineoplastic Combined Chemotherapy Protocols; Drug Synergism; Genes, p53; Humans; Imidazoles; Neoplasms; Piperazines; Proto-Oncogene Proteins c-mdm2; Tumor Suppressor Protein p53